Histomorfometria dos mecanorreceptores e terminações nervosas livres no quadril artrósico : estudo comparativo com quadril normal de cadáver - Moraes, Miguel Ricardo Barbosa (2008)
Proprioceptive studies have reported growing interest in investigators in the last few decades. This is result of relevant integrity of this system in the treatment of orthopedic diseases. Mechanoreceptors and free nerve endings are the microscopy basic units from proprioception and peripheral nervous system. They transmit to the central nervous system physiological information with detection threshold when the joint are submitted to mechanical stress. The presence and density of mechanoreceptors were investigated in the capsule, teres ligament and acetabulum labrum from 45 hips joint. Of these 30 were obtained from male patients (Group I) with secondary arthrosis at open arthoplasty and 15 of fresh cadaver with normal hip joint (Group II). The mean age of group I was 56,6 and the group II was 36,5 years. The fragments obtained were measured up to 2mm and stained with gold chloride 1%. After fixation the fragments were sectioned with cryostat at serial sections of 6µm thickness and examined using light microscopy. We identified 3 types of mechanoreceptors: Ruffini, Pacini and Golgi corpuscles, as well free nerve endings according of Freeman and Wike classified 1967. Each group was determined the number and density of mechanoreceptors and then it was compared. We conclude that the number of Pacini type was significative when it was compared with Rufini ( p < 0,01 ) and Golgi types (p< 0,001), in the normal group. However, the denstity of the Golgi type was minor compared to the Pacini ( p < 0,001) and free nerve ending ( p < 0,01 ) in the arthrosis group. Therefore, when the density total of nerve endings in normal hips were compared with arthosis hips we founded that the number decreased (p = 0.008). This is suggests strongly that the integrity of proprioceptive system seems to be modified by arthosis in consequence of nerve endings numbers. In the future, electrophysiological studies will be necessary to determine the rule of nerve endings and proprioceptive system in the normal and arthosis hip.